Implementation Of Independent Learning Curriculum Based On Environment In High School Country 1 City Lubuklinggau - Muspida, Muspida; Etty Safriyani; Wartono, Wartono (Sean Institute, 2025)
One approach that is relevant to the spirit of the Merdeka Belajar Curriculum is environment-based learning . Adiwiyata School is a school dedicated to environmental pedagogy and education . The study aims to determine the implementation of the environment-based independent learning curriculum at SMA N 1 Lubuklinggau. This study uses a qualitative approach with a case study design , to explore how the implementation of the environment-based Independent Learning Curriculum at SMA Negeri 1 Lubuklinggau City. The focus of the study is on the process, strategies, and obstacles faced in implementing the curriculum. The results of this study indicate that the implementation of the environment-based Independent Learning Curriculum can be an effective approach to improving the quality of learning while building students' environmental awareness. However, the success of this program is highly dependent on the full support of all parties involved, both internal and external to the school.